Biomarkers of fibrosis, kidney tissue injury and inflammation may predict severity and outcome of renal ANCA – associated vasculitis - Satrapova, Veronika; Sparding, Nadja; Genovese, Federica; Karsdal, Morten Asser; Bartonova, Lenka; Frausova, Doubravka; Honsova, Eva; Kollar, Marek; Suchanek, Miloslav; Koprivova, Helena; Rysava, Romana; Bednarova, Vladimira; et al. (Frontiers in Immunology, 2023)
Activity and chronicity of kidney involvement in ANCA-associated vasculitis (AAV) can be currently reliably evaluated only by kidney biopsy. In this study, we measured a panel of serum and urinary biomarkers collected at the time of kidney biopsy and hypothesized that they could reflect specific histopathological parameters in the biopsy and help to predict prognosis. We examined a cohort of 45 patients with AAV and 10 healthy controls. Biomarker levels (DKK-3, CD163, EGF, PRO-C6 and C3M) were measured in this study by ELISA. Biopsies were scored with a scoring system for AAV (focal x crescentic x sclerotic x mixed class) and interstitial fibrosis was quantified. Levels of urinary DKK-3, CD163, EGF, PRO-C6 and C3M significantly differed among biopsy classes in AAV, with urinary DKK-3 and PRO-C6 levels being highest in the sclerotic class and lowest in the focal class, urinary CD163 levels highest in the crescentic class and urinary C3M levels highest in the focal class. Moreover, the urinary biomarkers were able to discriminate focal biopsy class from the other classes. Urinary DKK-3, EGF, PRO-C6 and C3M levels measured at the time of biopsy were also significantly related to the extent of fibrosis and to the final kidney function at the end of follow-up. In conclusion, this small pilot study suggests that selected urinary biomarkers of fibrosis and inflammation may reflect changes in the kidney biopsy and be prognostic of kidney outcome in patients with AAV.